Remarks at the G20 Session on International Financial Architecture - Malpass, David (World Bank, Washington, DC, 2021)
World Bank Group President David Malpass remarked that early in the pandemic, the World Bank Group set out to use aggressive financial programming and leverage to increase commitments as rapidly as possible. The World Bank group used a number of powerful financial programming and leveraging techniques toward that goal. He highlighted recent capital increases, aggressive leveraging through bond issuance by IBRD, IDA and IFC, as well as MIGA reinsurance, and private sector mobilization, the combined WBG has been able to provide support to low- and middle-income countries over the last fifteen months. This financing is based on world-class knowledge work, and deep country relationships and know-how in our country teams present on the ground around the world. The World Bank Group strongly supports leveraging donor resources to maximize commitments, respond to emergencies, and prepare for crises. The World Bank Group provides grants to countries that are most in need, including fragile and small states and are investing heavily in social safety nets and digital cash transfer programs. Data sharing by both debtors and creditors enables debt reconciliation, a key for the debt restructuring process and he called on the G20 members to share their lending data and assist in the reconciliation exercise. The Group is actively implementing the Sustainable Development Finance Policy under IDA19 and will continue it in IDA20. The Group continues to strongly and actively support the implementation of the Common Framework, working closely with partners.